Antimicrobial Effect of Aqueous Extract of Moringa oleifera and Juniperus oxycedrus - Muftah Omar Ali, (AlQalam Journal of Medical and Applied Sciences, 2026)
The present study set out with the objective of investigating the effect of aqueous extracts of Moringa oleifera and Juniperus oxycedrus. leaves on four isolates of bacteria: two Gram-negative (Escherichia coli and Salmonella) and two Gram-positive (Streptococcus and Staphylococcus aureus). The estimation of antibacterial activity was conducted by utilising the Disc Diffusion Technique. The aqueous extracts of Moringa oleifera and Juniperus oxycedrus. leaves, when desiccated, are the subject of this study. The extract of Juniperus exhibited sensitivity at rates ranging from 0.2 to 0.7 mm to bacterial isolates of the gram-positive Streptococcus and Staphylococcus aureus, respectively. Furthermore, an inhibitory zone of 0.4 mm was demonstrated for both gram-negative E. coli and Salmonella. The aqueous extract of Moringa oleifera leaves demonstrated antibacterial properties, exhibiting inhibitory zones of 0.6 mm, 0.7 mm, and 0.1 mm against bacterial strains Streptococcus, Salmonella, and E. coli, consecutively. However, no inhibitory effect was observed against Staphylococcus aureus. A comprehensive investigation into the impact of varying concentrations of Moringa oleifera and Juniperus oxycedrus extracts on bacterial isolates, employing a range of solvents, is warranted.